La libertà universitaria sotto attacco in Brasile (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The election of Jair Messias Bolsonaro as President of the Republic on October 28, 2018 marked a radical change in Brazilian politics. This essay focuses on the limits imposed on university autonomy, as well as on freedom of teaching and opinion. More specifically, it observes the interventions put into effect by the Electoral Justice and the police in several universities throughout Brazil, in order to repress standard academic activities that were considered ‘illicit electoral propaganda’. The program of the current presidency includes the draft law on ‘School without party’, which invites students of primary and secondary schools to film with their mobile phones teachers who carry out activities deemed to be political ‘indoctrination’ and to upload those videos on a dedicated website. In Germany, a similar project is promoted by the extreme right-wing party ‘Alternative für Deutschland’ (AfD). However, in Germany intervening in such a way is more complex than in Brazil, thanks to the different organization of teaching (which is analyzed in the text). The climate of tension generated by these measures is documented by the Supremo Tribunal Federal’s sentence on these interventions and on the Chamber of Deputies’ draft law that should implement the ‘Programa Escola sem Partido’.